The effect of exercise on urinary gamma-glutamyl transferase and protein levels of volleyball players - (:unkn) unknown (EDIZIONI MINERVA MEDICA, 2006)
Aim. Postexercise proteinuria and increased urinary gamma-glutamyl transferase (GGT) levels can be indicative of exercise-induced renal damage. In the literature, there exists numerous studies on exercise-induced proteinuria; but studies investigating the effects of exercise on urinary GGT levels are quite few. We aimed to evaluate the effects of exercise on renal function, expressed through the exercise-induced differences in urinary GGT, creatinine and protein levels. Methods. The study was performed on 12 female and 12 male volleyball players of the same sports club. Urine samples collected before and 1 h after the exercise were analyzed for urinary GGT, creatinine and protein amounts. Results. No statistically significant difference was observed between pre- and postexercise urinary GGT levels (U/L and U/g creatinine) of female and male volleyball players (P>0.05). A significant exercise-induced increase in urinary protein excretion was observed for the male players, while a significant exercise-induced increase in urinary creatinine excretion was observed for the female players (P<0.05). When urinary GGT levels (U/L) were compared separately for setters and spikers, it was observed that female players had no significant difference, while male spikers had a statistically significant exercise-induced increase in the urinary GGT levels (U/L) (P<0.05). Conclusions. We suggest that the insignificance of the exercise-induced increases in the urinary parameters could be due to the relatively short-course of the exercise and the timing of postexercise urine collection. A comprehensive study performed on more subjects could yield results that are more significant.
Keywords: exercise; urine; gamma-glutamyl transferase; proteinuria; volleyball; POSTEXERCISE PROTEINURIA; PROLONGED EXERCISE; RENAL-FUNCTION; TRANSPEPTIDASE; HEMATURIA; CHILDREN; RUNNERS; BINDING; HUMANS